PREVALENCE AND CONTROL OF HYPERTENSION IN DIABETIC PATIENTS WITH VERSUS WITHOUT CHRONIC KIDNEY DISEASE. (June 2022) - Georgianou, E.; Markakis, K.; Georgianos, P.; Zografou, I.; Sachinidis, A.; Sabanis, C.; Doumas, M.
Abstract : Objective: Adequate control of hypertension is a guideline based strategy to retard the progression of kidney injury in patients with diabetes. The aim of this cross-sectional study was to compare the prevalence and control rates of hypertension in diabetic patients with versus without chronic kidney disease (CKD). Design and method: In 483 outpatients with type 1 or type 2 diabetes from a tertiary university hospital of the region of Thessaloniki, office blood pressure (BP) was recorded under standardized conditions (triplicate recordings after a 5-minute seated rest period) using the validated automated device HEM-705 (Omron, HealthCare). Hypertension was defined as office BP equal as or higher than 140/90 mmHg or current use of at least 1 antihypertensive drug. Results: The prevalence of hypertension was 69.8% in diabetic patients with estimated-glomerular-filtration-rate (eGFR) > 90 ml/min/1.73m2, 79.6% in patients with eGFR 60–90 ml/min/1.73m 2 and 91.4% in those with eGFR < 60 ml/min/1.73m 2 (P< 0.001 for the trend across eGFR strata). Despite the fact that 69.6% of the overall population was being treated with an average of 2.2 antihypertensive drugs daily, the control rates of hypertension were 41.8%, 40.0% and 34.5% in patients with eGFR > 90, 60–90 and < 60 ml/min/1.73m 2, respectively (P = 0.245). The decline in eGFR was accompanied by a parallel rise in systolic BP, decline in diastolic BP, and widening of pulse pressure (51.5 ± 14.8 vs. 55.5 ± 16.5 vs. 65.9 ± 17.3 mmHg in the eGFR strata of > 90, 60–90 and < 60 ml/min/1.73m 2, respectively, P < 0.001). A similar distribution of the severity of hypertension was observed when the patients were stratified by level of albuminuria. Conclusions: The present study shows that among patients with diabetes, the severity of hypertension increases in parallel with the decline in eGFR and rise in albuminuria. The widening of pulse pressure is possibly reflecting the more severe arteriosclerosis in patients with diabetes and established CKD.